2009
DOI: 10.4025/actascianimsci.v31i1.2745
|View full text |Cite
|
Sign up to set email alerts
|

Níveis de lisina e treonina digestíveis na ração de poedeiras comerciais sobre a qualidade de ovos

Abstract: Níveis de lisina e treonina digestíveis na ração de poedeiras Níveis de lisina e treonina digestíveis na ração de poedeiras Níveis de lisina e treonina digestíveis na ração de poedeiras Níveis de lisina e treonina digestíveis na ração de poedeiras comerciais sobre a qualidade de ovos comerciais sobre a qualidade de ovos comerciais sobre a qualidade de ovos comerciais sobre a qualidade de ovos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Matos et al (2009) found no effect (P> 0.05) of this variable when using different levels of digestible threonine (5.00, 5.50 and 6.00 g/kg); nor did Valerio et al (2000). This disagrees with the results of this work, possibly because the degree of interference with the internal quality of the eggs produced may be dependent on the strain of laying hens used; in addition, such factors as ambient temperature and the age of the hens may have an influence.…”
Section: Resultsmentioning
confidence: 88%
“…Matos et al (2009) found no effect (P> 0.05) of this variable when using different levels of digestible threonine (5.00, 5.50 and 6.00 g/kg); nor did Valerio et al (2000). This disagrees with the results of this work, possibly because the degree of interference with the internal quality of the eggs produced may be dependent on the strain of laying hens used; in addition, such factors as ambient temperature and the age of the hens may have an influence.…”
Section: Resultsmentioning
confidence: 88%
“…Matos et al (2006) trabalharam com poedeiras no período de 25 a 44 semanas e observaram interação entre os níveis de treonina e lisina para conversão alimentar (kg/kg). Esses autores recomendaram 0,800 e 0,550% de lisina digestível e treonina digestível, correspondente à relação treonina:lisina de 69%, para melhorar a conversão alimentar.…”
Section: Resultsunclassified
“…A relação treonina:lisina utilizada nas rações deste experimento foi de 75%. O nível de lisina digestível estimado neste experimento para melhor conversão alimentar (kg/kg) foi inferior ao recomendado por Matos et al (2006), de 75%, e esse resultado pode estar relacionado à relação treonina: lisina utilizada.…”
Section: Resultsunclassified
“…Other experiments showed that increasing the levels of digestible lysine of layer diets did not affect Haugh units (Jardim Filho et al, 2008;Schmidt et al, 2008;Matos et al, 2009;Rocha et al, 2009;Jardim Filho et al, 2010;Silva et al, 2010;), yolk index (Jardim Filho et al, 2008;Schmidt et al, 2008;Rocha et al, 2009;Jardim Filho et al, 2010), or total egg solids (Jardim Filho et al, 2008;Matos et al, 2009;Jardim Filho et al, 2010).…”
Section: Egg Quality Of Hens Fed Different Digestible Lysine and Argimentioning
confidence: 95%